Harmonisation of ESD Policies and Regulations from the Perspective of International Law and Constitutional Law to Support National Resilience - Zildjianda, Raesitha; Herlambang, Dian (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study aims to analyse the harmonisation of policies and regulations on Education for Sustainable Development (ESD) from the perspectives of international and constitutional law in Indonesia, and to examine its implications for strengthening national resilience. The research method used is a normative juridical approach.The results of the study indicate that harmonisation of ESD regulations in Indonesia is not optimal. From an international legal perspective, ESD is supported by soft law instruments. While constitutional law implicitly reflects ESD principles, ESD principles have not been systematically institutionalised. Key challenges include weak cross-sectoral coordination, limited institutional capacity, and disparities in implementation across regions. However, there are opportunities for strengthening through global commitments, national policies, technological developments, and multi-stakeholder participation. This study confirms that harmonising ESD policies and regulations is a strategic step in developing sustainable human resources and strengthening national resilience. Therefore, strengthening integrated regulations, improving institutional coordination, and developing human resource capacity are necessary to optimise ESD implementation in Indonesia.